Relevance of Variations in the Opposing Dentition for the Functionality of Fixed and Removable Partial Dentures: A Systematic Review - Bernhard Pommer; Martin Krainhöfner; Georg Watzek; Gabor Tepper; Charalabos-Markos Dintsios (International Journal of Dentistry)
The aim of this systematic review was to evaluate the functionality of fixed and removable partial dentures as test interventions in relation to variations in the opposing dentition and their prosthetic restoration. The abstracts identified in the respective databases were screened independently by two investigators. RCTs and uncontrolled studies were considered, provided the patients were included consecutively and the confounding variables were adequately monitored. Seventeen papers were included. The study and publication quality was assessed using a “biometric quality” tool showing an overall poor quality. The reported outcomes, such as survival rates, were in each case obtained from a single study. Two possible trends could be deduced for the endpoint longevity: (a) the first trend in favor of removable partial dentures, compared to fixed partial dentures, with a fully edentulous opposing arch fitted with a removable prosthesis; (b) the second trend in favor of implant-supported partial dentures, compared to conventionally fixed partial dentures, with natural opposing dentition or with a removable partial denture in the opposing arch. No evidence could be generated as to whether, and if so how, variations in the opposing dentition have a bearing on the decision to fit a partially edentulous arch with a fixed or removable partial denture.